Fruiting bodies of Aspergillus: An unusual finding in histopathology - Anila, K. R. (Medknow Publications & Media Pvt Ltd, 2013)
A-62-year-old lady presented with complaints of cough, dyspnea and hemoptysis of 3 months duration. A radiological evaluation revealed a mass lesion in the left lung along with significant lymphadenopathy. With a clinical and radiological diagnosis of carcinoma of the lung, the patient was taken up for biopsy. The specimen consisted mainly of grey-white friable soft-tissue, which on histopathological evaluation showed small cell carcinoma, which was confirmed with immunohistochemistry. Apart from the carcinomatous component, many hyphae and fruiting bodies of Aspergillus were also seen. We are reporting this case because, though the finding of hyphal forms of Aspergillus is not so uncommon in lung biopsies, detection of fruiting bodies of Aspergillus in histopathological section is an extremely rare finding. The hyphal forms of Aspergillus can be confused with the hyphal forms of other fungi, but when fruiting bodies are present a definite diagnosis is possible at the histopathology level itself. We would also like to highlight that contamination should be excluded before labeling a case as Aspergillosis because of the potentially toxic medication implicated in the treatment.